If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7ab + ab + -9ab = 0 Combine like terms: 7ab + ab = 8ab 8ab + -9ab = 0 Combine like terms: 8ab + -9ab = -1ab -1ab = 0 Solving -1ab = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Divide each side by '-1'. ab = 0 Simplifying ab = 0 The solution to this equation could not be determined.
| 0.66a=6 | | 3x+0+8=0 | | 3x^3-13x^2+12x-6=0 | | 9x-7y=y | | 10x-y=12 | | X+.75y=15 | | -(8-b)+12b-9=-6b+2b | | 1=x-6 | | 3(2x-1)+2=5x-1 | | x+4y+2z=0 | | 2x-3y+2=2 | | 6+4a=-8 | | 0.66r=8 | | 72=-3(x+4)-21x | | K-7=10 | | 3+z=18 | | 1.5r=8 | | -5x=18-3x | | 0.8m=80 | | -6+4y=-12 | | 5x-4(x-6)=1 | | h=-16t^2+150t+1 | | 2x+y=10-3x | | 2x^2-15x+15=8-x^2-5x | | (u+3)2=2u+11u+15 | | X^4-7x+3=0 | | 2x^4-7x+3=0 | | 2x+3x-15=25 | | -2+x-4x=11 | | 5(6)+3(7)= | | -4+3x=-12+25xfraction | | 2y-4*0=10 |